Transforming Social Behavior in Society through the Implementation of Digital Literacy - B. Ngenget, Edmundus (Journal of World Science, 2022)
Globalization is a necessity that cannot be avoided, as well as the rapid flow of technology. So, people must be able to react wisely. This is because, if people are not digital literate and blind to digital literacy, the easy situation will actually become a boomerang for themselves and others, such as the occurrence of various crime cases in online and offline media. Digital literacy is predicted to be able to overcome problems regarding various ignorance in utilizing digital which of course affects various aspects. For this reason, the researcher wants to find out more about the transformation of social behavior in society through digital implementation. The method used is descriptive quantitative by selecting respondents through purpose sampling which is adjusted to the research objectives, then the process of obtaining data using surveys which are distributed to all respondents. In addition to surveys, observation and interviews are also used to increase the validity of the research results. The results of the study show that the transformation of social behavior goes from bad to better which is seen from the mindset and culture and then forms social behavior in the community that seems to have changed. Where they can think more critically, improve the quality of culture and not be careless when they behave, they also help to harmonize society through the social behavior displayed.